2006
DOI: 10.1242/jeb.02369
|View full text |Cite
|
Sign up to set email alerts
|

Visual stimulation of saccades in magnetically tetheredDrosophila

Abstract: turns averaging 35°in 80·ms, similar to the kinematics of free flight saccades. Our results indicate that tethered and free flight saccades share a common neural basis, but that the lack of appropriate feedback signals distorts the behavior performed by rigidly fixed flies. Using our new paradigm, we also investigated the features of visual stimuli that elicit saccades. Our data suggest that saccades are triggered when expanding objects reach a critical threshold size, but that their timing depends little on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
144
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(161 citation statements)
references
References 48 publications
16
144
1
Order By: Relevance
“…For example, horizontal edges generate vertical motion, whereas vertical edges generate horizontal motion and both cues trigger saccades equally well. 6 The extent to which different directional motion cues contribute to the control of flight speed and visual depth in flies is unknown. Here, we manipulated the orientation of motion cues, and measured the impact on these behavioral variables.…”
Section: Introductionmentioning
confidence: 99%
“…For example, horizontal edges generate vertical motion, whereas vertical edges generate horizontal motion and both cues trigger saccades equally well. 6 The extent to which different directional motion cues contribute to the control of flight speed and visual depth in flies is unknown. Here, we manipulated the orientation of motion cues, and measured the impact on these behavioral variables.…”
Section: Introductionmentioning
confidence: 99%
“…This important effect is, of course, entirely removed in studies that rigidly tether insects (12). Even in experimental preparations that loosely confine the motion of insects (23,24), turning kinematics are different from those observed in free-flight studies (10,15,25). These discrepancies indicate that restrictive preparations interfere with flight behavior, and the results of such studies must be interpreted in light of this influence.…”
mentioning
confidence: 95%
“…This is plausible since such an approach should lead to an almost symmetrical activity in the two sensory input neurons which is transformed to only small saccade amplitudes by the saccadic controller. The generation of large saccades in response to strong frontal expansion flow, as discussed recently for Drosophila (Bender and Dickinson 2006) could solve this problem. Similar mechanisms to avoid frontal expansion were also proposed (Neumann 2004) and successfully tested on robots (Webb et al 2004).…”
Section: Discussionmentioning
confidence: 98%
“…Nonetheless, it is not clear so far what triggers saccades in blowflies. For the fruit fly Drosophila, it was concluded that a visual trigger feature for saccades is fronto-lateral image expansion (Bender and Dickinson 2006;Tammero and Dickinson 2002a,b).…”
Section: Introductionmentioning
confidence: 99%